(untitled) (Andamios, Revista de Investigación Social, 2025)
This article presents the results of a research that analyzed the forms of bioresistance of the Weras, an ecofeminist collective that emerged in 2021 in Pereira, Colombia. In addition to direct social participation during the social outburst of 2021 in this country, semi-structured interviews were conducted with two of the founders of this collective and a content analysis of their social network Instagram was implemented. It is concluded that bioresistances of Weras collective confront juvenicide in Colombia and constitute life alternatives based on logics of communication, cooperation, trust and construction of the common. An original contribution is made to youth studies from an experience that has not been analyzed to date.